Advanced materials for concrete-filled tubular columns and connections. (November 2015) - Espinos, Ana; Romero, Manuel L.; Hospitaler, Antonio; Pascual, Ana M.; Albero, Vicente
Abstract: The advantages of concrete-filled steel tubular (CFST) columns are well known at room and elevated temperatures, however, beyond a certain slenderness their load-bearing capacity starts to decrease. Besides, blind-bolts represent a proper system to allow endplate bolted connections to hollow steel tubular columns and CFST, although the resistance of the bolt shank conditions affects the performance of the connection. In this paper, the use of innovative materials is proposed as a method of enhancing of the load-bearing capacity for both CFST columns and connections. In this line, a first approach of the benefits using high strength steel, fire-resistant steel and geopolymer concrete applied for CFST columns in the fire situation is developed, obtaining better fire results although depending on the columns cross-sections configuration and the part where the advanced material is applied. Related to blind-bolts connections under fire conditions, the use of fire-resistant bolts is assessed. Their higher strength retention in fire could avoid the use of protection, but only in limited cases. Furthermore, a preliminary study on shape memory alloys in the blind-bolts is performed at room temperature and supporting cyclic pull-out loading.